(The efficiency of decision-making in light of the adoption of strategic intelligence hubs in the Jordanian Customs Department (field study - Al-Ta‘ani, Enad (Journal of Economic, Administrative and Legal Sciences, 2017)
The idea of the studying is summarized on measuring the output of the actual application of the main elements to the strategic intelligence in the Jordanian Customs Department, and the impact of the strategic decision in the department and development its performance ,and the departments taking care of the staff. and the officials awarness,especially those who work in the branch of institutional development and planning ,for strategic planning axes. The main purpose for using descriptive and analytical approach in the research is, on one hand, for proving the importance of the elements of the strategic intelligence in the custom’s department. on the other hand, the consequences of the use of these elements on strategic planning in the department.Thus,the researcher had done afield study on the targeted community.i.e. the employments of Custom s department from different administrative levels for both the supervisory and executive. The analysis of the studying depended on all the statistical systems which the researcher believes that it serves the studying purpose , and helps in giving real results which reflect the studying inputs . The most important results of the studying are the positive relationship and the development of the work environment in the light of using the Customs department for the elements of the strategic intelligence( Supervision ,Strategic Vision ,Employee s motivating , Strategic alliances , regular thinking ) . In addition , there was an important result shows that the department is implicitly using the elements of the strategic intelligence.